Inverted radial Alfvén continua: first results from “heliophysics audified: resonances in plasmas” - Hartinger, Michael D.; Archer, Martin O.; Masongsong, Emmanuel; Shi, Xueling; Alexander, Robert; Vidugiris, Evaldas; Holland, Anne; Harold, James; Laca, Jasper; Blum, Lauren W.; Coyle, Shane; Candey, Robert M.; et al. (Frontiers in Astronomy and Space Sciences, 2026)
Ultra Low Frequency (ULF) waves with periods of ∼10–1,000 s can lead to space weather impacts such as induced electrical currents in power grids, thus it is important to understand the factors controlling wave dynamics. This is challenging, however, as waves (1) are affected by multiple factors simultaneously, (2) are non-stationary which in some cases precludes use of identification methods that assume stationarity, (3) can occur in superposition with each other making them difficult to separate and identify. Past studies have addressed these challenges through combined audiovisual analysis tools to identify complex but recurring patterns in ULF wave activity that eluded standard visual inspection and automated detection algorithms, as well as through crowd-sourced wave identification. The “Heliophysics Audified: Resonances in Plasmas” NASA citizen science project follows these studies by deploying a Graphical User Interface (GUI) for crowd-sourced ULF wave identification to a large online audience before and during the Heliophysics Big Year (HBY). In this study, we discuss the initial development, beta testing, and deployment of the GUI in April 2023. We further discuss the key initial scientific findings of the HARP project, in particular the discovery by volunteers of anomalous standing Alfvén wave activity with frequency increasing with distance from the Earth. Finally, we discuss participant impacts and lessons learned, as well broader impacts beyond the scope of the original project such as collaborations with museums and musicians. We place these results in context with previous work and discuss implications for future studies.